Humanistic Personality in Andrea Hirata’s Novel Padang Bulan - Lefia, T (KnE Social Sciences, 2018)
The aim of this study is to analyse Maryamah’s Humanistic Personality in Andrea Hirata’s novel Padang Bulan. The research method applied in this research is Library research. There are two data used in this research, namely primary data and secondary data. The primary data are taken from the novel itself, Padang Bulan. The secondary data are document, script and other relevant sources which provide the information related to this analysis. The approach used in this research is Abraham Maslow’s theory of Psychology of Humanistic Personality in Schultz (1977). Maryamah is a persistent and diligent Person to meet the need of her life. This is the basis for the selection of Padang Bulan as an object for research. The Humanistic Personality as the aspect studied in Padang Bulan is in accordance with the struggles of the main character to meet her needs, including Physiological Needs, safety Needs, Need of Love, Belonging, esteem Needs, and self actualization Needs and the findings show that all these needs are clearly exposed in the novel showing that the protagonist has got humanistic personality. Keywords: humanistic personality, struggle, psychology